SPIRITUAL PSYCHOTHERAPY EFFECT TO INCREASE CD4+ COUNT IN HIV /AIDS PATIENTS - M Faisal Idrus; Jayalangkara Jayalangkara; Syamsu Syamsu; Ilham Ilham (Nusantara Medical Science Journal, 2016)
ABSTRACT  Introduction: HIV / AIDS is a viral infection that causes decrease of immunity system characterized by decrease CD4+ T lymphocyte counts. Low CD4 T-cell counts are considered due to destruction of lymphocytes T by human immunodeficiency virus. The spiritual psychotherapy is a form of psychiatric treatment that provides peace, and happiness of the soul. Peace of mind is expected to generate individual immune response. Objectives: Objective  to determine the effect of spiritual psychotherapy to CD4 T-cell count. Methods: This is a quasi experimental study pretest-posttest control group design of 40 sample with HIV / AIDS who were selected by purposive sampling. This research was conducted in the HIV / AIDS Working Group and hospital inpatient BLU. Dr. Wahidin Sudirohusodo. Makassar. The samples were divided into two groups, the treatment group of 10  inpatient who received intensive spiritual psychotherapy, 10 sample from Lapas Bolangi and 20 control group who did not receive supportive psychotherapy. Statistical analysis using the Wilcoxon test. Results: The results of the analysis of CD4 + serum between the treatment and control groups was significantly different (p<0.05). After treatment, the CD4 T-cell count in the inpatient group increased serum from 15 to 160, but  in the other groups (group bolangi from 446.50 to 365.50 and the control group from 424.5 to 201.0) was decreased, especially in the control group (Tables 2 and 3). Table 4 shows that of the 10  inpatient samples group, all had increased levels of CD4 + serum, whereas in the group Bolangi only 3 samples (30%) among the 10 sample of the control group , of 20 sample only 1 person (5%) had increase of CD4 + serum , and 19 sample (95%) had decrease.   Keywords: Spiritual Psychotherapy – relaxation - CD4 count